2014
DOI: 10.1186/1471-2482-14-97
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbidities on postoperative complications in patients undergoing laparoscopy-assisted gastrectomy for gastric cancer

Abstract: BackgroundComorbidity is a predictor of postoperative complications (PCs) in gastrectomy. However, it remains unclear which comorbidities are predictors of PCs in patients who undergo laparoscopy-assisted gastrectomy (LAG). Clinically, insufficient lymphadenectomy (LND) is sometimes performed in high-risk patients, although the impact on PCs and outcomes remains unclear.MethodsWe retrospectively studied 529 patients with gastric cancer (GC) who underwent LAG. PCs were defined as grade 2 or higher events accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…15,40 In our study, a history of cardiac disease was an independent predictor of readmission. Previous studies have also identified a relationship between cardiac disease and post-operative morbidity and hospital readmission 13,41,42 including a metaanalysis by Fisher et al which evaluated the factors associated with readmission after pancreatic surgery. 43 Although the exact mechanism by which patients with cardiac disease are at risk of readmission is unclear, it is likely that such patients have less capacity to respond to complications due to a lower physiological reserve.…”
Section: Hpbmentioning
confidence: 99%
“…15,40 In our study, a history of cardiac disease was an independent predictor of readmission. Previous studies have also identified a relationship between cardiac disease and post-operative morbidity and hospital readmission 13,41,42 including a metaanalysis by Fisher et al which evaluated the factors associated with readmission after pancreatic surgery. 43 Although the exact mechanism by which patients with cardiac disease are at risk of readmission is unclear, it is likely that such patients have less capacity to respond to complications due to a lower physiological reserve.…”
Section: Hpbmentioning
confidence: 99%
“…2-4 SSI rates are also influenced by preoperative comorbidities. [5][6][7] In the current study, we report the impact of significant MDR-GNB colonization and concurrent comorbidity on SSI and long-term surgical outcomes.The current retrospective study was conducted among patients operated for endometrial cancer in an oncology center in eastern India between 2011 and 2016. In total, 150 patients underwent gynecological oncosurgery during this period.…”
mentioning
confidence: 99%
“…[2][3][4] SSI rates are also influenced by preoperative comorbidities. [5][6][7] In the current study, we report the impact of significant MDR-GNB colonization and concurrent comorbidity on SSI and long-term surgical outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…D1+ can be an alternate for D2 in highrisk patients [104] . Inokuchi et al [105] suggested that the presence of heart or liver disease is a significant risk factor for postoperative morbidity in patients who undergo laparoscopic gastrectomy. Although it did not reduce complications, insufficient LN dissection (for example, D1+ for advanced gastric cancer) might be permissible in highrisk patients as it had no negative impact on gastric cancerspecific survival.…”
Section: Resultsmentioning
confidence: 99%